A Dalit Mainstreaming in Rural Development: An Alternative Approach for Combating Poverty - Pasa, Rajan Binayek; Bishwokarma, Lila Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2020)
Rajan Binayek Pasa (Ph.D. in Education, 2019 and Ph.D. Scholar in Rural Development) is Assistant Professor at Central Department of Rural Development (CDRD), Tribhuvan University, University Campus Kirtipur Kathmandu. Besides, he has been serving as a coordinator of Self Study Report preparation committee of CDRD that is formed under Quality Accrediation Assurance project of University Grants Commission Nepal. Pasa’s publications within education and social sciences are more focused on transformative role of education, employability of technical education and vocational training, agriculture transformation, ecotourism and rural tourism development issues.